HELLP Syndrome and Cerebral Venous Sinus Thrombosis Associated with Factor V Leiden Mutation during Pregnancy - Zeynep Ozcan Dag; Yuksel Işik; Yavuz Simsek; Ozlem Banu Tulmac; Demet Demiray (Case Reports in Obstetrics and Gynecology)
Preeclampsia is a leading cause of maternal mortality and morbidity worldwide. The neurological complications of preeclampsia and eclampsia are responsible for a major proportion of the morbidity and mortality for women and their infants alike. Hormonal changes during pregnancy and the puerperium carry an increased risk of venous thromboembolism including cerebral venous sinus thrombosis (CVST). Factor 5 leiden (FVL) is a procoagulant mutation associated primarily with venous thrombosis and pregnancy complications. We report a patient with FVL mutation who presented with CVST at 24th week of pregnancy and was diagnosed as HELLP syndrome at 34th week of pregnancy.